High-stability core-shell structure silicon negative electrode material as well as preparation method and application thereof
By forming the chemical bond between the high-entropy stable shell and the high-capacity silicon core in situ on the silicon negative electrode material, the stress problems caused by volume changes and poor interface stability of the silicon negative electrode material are solved, and high stability and excellent electrochemical performance are achieved.
Patent Information
- Application Number
- CN202510028272.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-15
AI Technical Summary
The stress caused by volume changes during the charge and discharge process of silicon negative electrode materials leads to the crushing and reconstruction of the solid electrolyte layer, which consumes active materials and electrolyte, resulting in rapid attenuation of lithium storage capacity. The existing surface coating strategy has the problems of large interface contact resistance and poor stability.
The highly entropy stable shell is formed in situ by mechanical mixing and high-temperature heat treatment, and is bonded to the high-capacity silicon core through chemical bonding to form a high-stable core-shell structure silicon negative electrode material, reducing the interface contact resistance and improving the stability of the electrolyte contact interface.
It significantly improves the structural stability and ion/electron transmission performance of silicon negative electrode materials, achieves high charge and discharge specific capacity, excellent cycle stability and rate performance, and at the same time, it is simple in process, low cost and low energy consumption, making it suitable for large-scale production.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of preparation of negative electrode materials for lithium-ion batteries, and specifically relates to a highly stable core-shell structured silicon negative electrode material, a preparation method and uses thereof, and in particular to a high-entropy stable shell layer of a silicon negative electrode material, a preparation method thereof and uses thereof in lithium-ion batteries. Background Art
[0002] With the rapid development of portable electronic devices and electric vehicles, the research on energy storage devices with high energy density, high power density and long cycle life has become the focus of global attention. The development of high-performance electrode materials is one of the key technologies to break through the energy density bottleneck of lithium-ion batteries represented by traditional graphite negative electrodes, and is also a research hotspot in the field of electrochemical energy storage.
[0003] Silicon anode materials have become a kind of lithium-ion battery anode materials with great practical application potential due to their high theoretical specific capacity and low lithiation potential. However, the stress generated by the huge volume change during the charge and discharge process causes the solid electrolyte layer to break and rebuild, continuously consumes silicon active materials and electrolyte, and the lithium storage capacity decays rapidly, which is difficult to meet the needs of practical applications. Surface coating is one of the effective measures to solve the problem of interface instability of silicon anode materials, but the current surface coating strategies usually face problems such as large interface contact resistance and poor interface stability, making it difficult to achieve high-rate performance of silicon anode materials. In addition, the reaction between the coating layer and the electrode liquid causes a large amount of electrode liquid to be consumed during the first discharge process, resulting in low first coulombic efficiency.
[0004] Therefore, the art hopes to develop a simple, low-cost, and scalable method to prepare a highly stable shell layer on the silicon surface, effectively improve the structural stability of the silicon negative electrode material and obtain an interfacial fast ion / electron transport path. Summary of the invention
[0005] In view of the above problems existing in the prior art, the purpose of the present invention is to provide a highly stable core-shell structure silicon negative electrode material and its preparation method and use. In the highly stable core-shell structure silicon negative electrode material involved in the present invention, the high entropy stable shell layer formed in situ is bonded to the high-capacity silicon core by chemical bonds to form an integrated highly stable core-shell structure, which is an ideal lithium-ion battery negative electrode material, showing excellent stability and ion / electron transmission performance, and the prepared battery has high charge and discharge specific capacity, extremely excellent cycle stability and rate performance; moreover, the preparation process of the present invention is simple, low cost, low energy consumption, can realize large-scale production, and has broad application prospects.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a highly stable core-shell structured silicon negative electrode material, wherein the negative electrode material comprises a covalently bonded high-capacity silicon core and a high-entropy shell.
[0008] In the silicon negative electrode material of the present invention, the high entropy shell is formed in situ through mechanical mixing of different elemental single substances and (or) compounds and a high-temperature heat treatment process, and is interconnected with the high-capacity silicon core through covalent bonds, effectively reducing the interface contact resistance and promoting the rapid interface transport of ions / electrons; in addition, the high entropy shell effectively improves the stability of the electrolyte contact interface, avoids the continuous loss of electrode liquid and silicon active materials during the charge and discharge process, and effectively promotes the rapid diffusion of ions and slows down the electrode polarization.
[0009] Preferably, the silicon material may be a silicon material of different dimensions, such as silicon nanoparticles, silicon micron particles, silicon nanowires, silicon nanotubes and (or) silicon nanosheets, etc., preferably including any one of silicon nanoparticles, silicon nanowires, silicon nanotubes and (or) silicon nanosheets or a mixture of at least two thereof, and typical but non-limiting examples of the mixture include: a mixture of nanoparticles and silicon nanowires, a mixture of silicon nanoparticles and silicon nanosheets, a mixture of silicon nanoparticles, silicon nanowires and silicon nanosheets, etc. However, it is not limited to the silicon nanomaterials listed above, and other silicon materials commonly used in the art may also be used in the present invention.
[0010] Preferably, the different element single substances and (or) compounds are mixtures of any four elements and (or) compounds of indium, tin, gallium, copper, zinc, phosphorus, sulfur, nitrogen, oxygen, carbon, tin oxide, phosphorus pentoxide, copper nitrate, zinc nitrate, copper sulfate, tin chloride, copper chloride, etc., and typical but non-limiting examples of the mixture include: a mixture of indium, tin, gallium, and zinc, a mixture of zinc, phosphorus, sulfur and nitrogen, a mixture of nitrogen, oxygen, carbon and tin oxide, a mixture of carbon, tin oxide, phosphorus pentoxide and copper nitrate, and a mixture of indium, tin, gallium, copper, zinc and phosphorus.
[0011] Preferably, in the negative electrode material, the thickness of the high entropy stable shell is 1-10 nm, for example, 0.5 nm, 1.0 nm, 1.1 nm, 1.2 nm, 1.5 nm, 2.5 nm, 3.0 nm, 4.0 nm, 5.0 nm, 5.5 nm, 6.5 nm, 7.5 nm, 9.5 nm or 10 nm.
[0012] Preferably, the high entropy stable shell contains no less than 5 types of elements.
[0013] In a second aspect, the present invention provides a method for preparing the highly stable core-shell structure silicon negative electrode material as described in the first aspect, the method comprising the following steps:
[0014] The silicon negative electrode material and any four or more elements and (or) compounds are mechanically mixed, and then the uniform mixture is subjected to high-temperature heat treatment in a non-oxidizing atmosphere to obtain a core-shell structured silicon negative electrode material with a high-entropy stable shell layer.
[0015] In the present invention, after the mixing step, simple substances and (or) compounds of different elements are uniformly mixed with the silicon material and adsorbed on the surface thereof.
[0016] In the method of the present invention, after the heat treatment step, different elements penetrate into the surface of the silicon material to form a high entropy stable shell in situ.
[0017] Preferably, the mixing equipment used for the mechanical mixing is any one of a propeller agitator, a spiral agitator, a mincer, a pulverizer, a crusher, and a ball mill, but is not limited to the mechanical mixing methods listed above. Other commonly used methods in the art can also be used in the present invention.
[0018] Preferably, the silicon material includes any one of zero-dimensional silicon particles, one-dimensional silicon wires / tubes or two-dimensional silicon wafers, or a mixture of at least two of them, but is not limited to the silicon nanomaterials listed above. Other silicon materials commonly used in the art can also be used in the present invention.
[0019] Preferably, the mixing time is 10 min-24 h, for example, 10 min, 15 min, 17 min, 20 min, 25 min, 30 min, 35 min, 40 min, 60 min, 1 h, 2 h, 3 h, 5 h, 7 h, 9 h, 10 h or 24 h, etc., preferably 20 min.
[0020] Preferably, the heat treatment method is any one of high temperature furnace heating, Joule heating, and microwave heating, but is not limited to the heat treatment methods listed above. Other commonly used methods in the art can also be used in the present invention.
[0021] Preferably, the heat treatment temperature is 400°C-3000°C, for example, 400°C, 450°C, 500°C, 600°C, 650°C, 675°C, 700°C, 750°C, 760°C, 780°C, 800°C, 850°C, 880°C, 900°C, 925°C, 1950°C, 2550°C or 3000°C, etc., preferably 800°C.
[0022] Preferably, the heat treatment time is 10 min-24 h, for example, 0.5 h, 1 h, 2 h, 3 h, 5 h, 7 h, 10 h, 12 h, 13 h, 15 h, 16 h, 18 h, 20 h, 21 h, 22 h, 23 h or 24 h, etc., preferably 2 h.
[0023] Preferably, the non-oxidizing atmosphere is any one of nitrogen, argon, hydrogen, helium or carbon dioxide, or a combination of at least two of them. Typical but non-limiting examples of the combination include: argon atmosphere, argon / hydrogen mixed atmosphere, etc.
[0024] In a third aspect, the present invention provides a negative electrode active material for a battery, wherein the negative electrode is the highly stable core-shell structure silicon negative electrode material as described in the first aspect.
[0025] In a fourth aspect, the present invention provides an electrochemical energy storage device and / or energy storage system, characterized in that the electrochemical energy storage device and / or energy storage system comprises the highly stable core-shell structure silicon negative electrode material described in the first aspect.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] (1) The present invention utilizes mechanical mixing and high temperature heat treatment to in situ form a high entropy stable shell layer to improve the rate performance and cycle stability of silicon negative electrode materials;
[0028] (2) The present invention utilizes chemical bonds to bond the high entropy stable shell layer to the high capacity silicon core to form an integrated high stable core-shell structure, which significantly reduces the interface contact resistance and stabilizes the electrolyte contact interface;
[0029] (3) The present invention has the advantages of simple preparation process, low energy consumption, scalability, and compatibility with existing electrode preparation processes, and has good application prospects. DETAILED DESCRIPTION
[0030] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0031] Example 1
[0032] In this embodiment, a highly stable core-shell structure silicon negative electrode material is prepared by the following method, which specifically includes the following steps:
[0033] (1) mechanically mixing silicon nanoparticles, indium, tin, gallium and copper in a mass ratio of 96:1:1:1:1;
[0034] (2) The mixture obtained in step (1) was heat treated at 800° C. in a hydrogen / argon mixed atmosphere for 2 h (temperature increase of 5° C. / min) to obtain a highly stable core-shell structure silicon negative electrode material, wherein the high entropy stable shell layer thickness is 5 nm.
[0035] The obtained silicon negative electrode was used as the negative electrode active material, and the negative electrode active material, conductive agent (acetylene black) and binder (sodium alginate) were uniformly mixed to form a slurry, which was coated on a copper foil current collector and rolled to form a negative electrode sheet after vacuum drying at 70°C for 2 hours. The negative electrode sheet was used as the test electrode, metallic lithium was used as the counter electrode, a mixed solution of ethylene carbonate and diethyl carbonate dissolved with lithium hexafluorophosphate was used as the electrolyte (1 mol / LLiPF6 / EC:DEC, the volume ratio of EC and DEC was 1:1), and Celgard 2400 polypropylene film was used as the separator. A button-type lithium-ion battery was assembled in a glove box with oxygen and water contents less than 0.1 ppm. At a current density of 0.5 C, the obtained battery has a capacity of up to 1380 mAh g -1 After 200 cycles, the capacity retention rate can reach 92%, which has extremely excellent cycle stability.
[0036] Example 2
[0037] In this embodiment, a highly stable core-shell structure silicon negative electrode material is prepared by the following method, which specifically includes the following steps:
[0038] (1) mechanically mixing silicon nanoparticles, indium, tin, gallium and copper in a mass ratio of 92:2:2:2:2;
[0039] (2) The mixture obtained in step (1) was heat treated at 800° C. in a hydrogen / argon mixed atmosphere for 2 h (temperature increase of 5° C. / min) to obtain a highly stable core-shell structure silicon negative electrode material, wherein the high entropy stable shell thickness is 8 nm.
[0040] The obtained silicon negative electrode was used as the negative electrode active material, and the negative electrode active material, conductive agent (acetylene black) and binder (sodium alginate) were uniformly mixed to form a slurry, which was coated on a copper foil current collector and rolled to form a negative electrode sheet after vacuum drying at 70°C for 2 hours. The negative electrode sheet was used as a test electrode, metallic lithium was used as a counter electrode, a mixed solution of ethylene carbonate and diethyl carbonate dissolved with lithium hexafluorophosphate was used as an electrolyte (1 mol / LLiPF6 / EC:DEC, the volume ratio of EC and DEC was 1:1), and Celgard 2400 polypropylene film was used as a separator. A button-type lithium-ion battery was assembled in a glove box with oxygen and water contents less than 0.1 ppm. At a current density of 0.5 C, the obtained battery has a capacity of up to 1260 mAh g -1 The weight specific capacity of the battery can reach 98% after 200 cycles, which shows excellent cycle stability.
[0041] Example 3
[0042] In this embodiment, a highly stable core-shell structure silicon negative electrode material is prepared by the following method, which specifically includes the following steps:
[0043] (1) mechanically mixing silicon nanoparticles, indium, tin, gallium, phosphorus oxide, and copper nitrate in a mass ratio of 92:1:1:2:2:2;
[0044] (2) The mixture obtained in step (1) is subjected to Joule heating treatment at 2500° C. in a hydrogen / argon mixed atmosphere for 10 min to obtain a highly stable core-shell structure silicon negative electrode material, wherein the thickness of the high entropy stable shell layer is 7 nm.
[0045] The obtained silicon negative electrode was used as the negative electrode active material, and the negative electrode active material, conductive agent (acetylene black) and binder (sodium alginate) were uniformly mixed to form a slurry, which was coated on a copper foil current collector and rolled to form a negative electrode sheet after vacuum drying at 70°C for 2 hours; the negative electrode sheet was used as the test electrode, metallic lithium was used as the counter electrode, a mixed solution of ethylene carbonate and diethyl carbonate dissolved with lithium hexafluorophosphate was used as the electrolyte (1 mol / L LiPF6 / EC:DEC, the volume ratio of EC and DEC was 1:1), and Celgard 2400 polypropylene film was used as the separator, and a button-type lithium-ion battery was assembled in a glove box with oxygen and water contents less than 0.1 ppm. At a current density of 0.5 C, the obtained battery has a capacity of up to 1350 mAh g -1 The weight specific capacity of the battery can reach 98% after 200 cycles, which shows excellent cycle stability.
[0046] Comparative Example 1
[0047] In this comparative example, silicon nanoparticles were placed in a high temperature tube furnace, heated to 750° C. in an argon atmosphere, introduced with 200 sccm of acetylene, reacted for 10 min, and cooled to room temperature in an argon atmosphere to obtain a carbon-coated silicon core-shell structure material.
[0048] The obtained silicon negative electrode was used as the negative electrode active material, and the negative electrode active material, conductive agent (acetylene black) and binder (sodium alginate) were uniformly mixed to form a slurry, which was coated on a copper foil current collector and rolled to form a negative electrode sheet after vacuum drying at 70°C for 2 hours; the negative electrode sheet was used as the test electrode, metallic lithium was used as the counter electrode, a mixed solution of ethylene carbonate and diethyl carbonate dissolved with lithium hexafluorophosphate was used as the electrolyte (1 mol / L LiPF6 / EC:DEC, the volume ratio of EC and DEC was 1:1), and Celgard 2400 polypropylene film was used as the separator, and a button-type lithium-ion battery was assembled in a glove box with oxygen and water contents less than 0.1 ppm. At a current density of 0.5 C, the obtained battery has a capacity of up to 1120 mAh g -1 The weight specific capacity of the battery can reach 88% after 200 cycles, which shows excellent cycle stability.
[0049] Comparative Example 2
[0050] In this comparative example, silicon nanoparticles were placed in a high temperature tube furnace, heated to 750° C. in an argon atmosphere, introduced with 200 sccm of methane, reacted for 10 min, and cooled to room temperature in an argon atmosphere to obtain a carbon-coated silicon core-shell structure material.
[0051] The obtained silicon negative electrode was used as the negative electrode active material, and the negative electrode active material, conductive agent (acetylene black) and binder (sodium alginate) were uniformly mixed to form a slurry, which was coated on a copper foil current collector and rolled to form a negative electrode sheet after vacuum drying at 70°C for 2 hours; the negative electrode sheet was used as the test electrode, metallic lithium was used as the counter electrode, a mixed solution of ethylene carbonate and diethyl carbonate dissolved with lithium hexafluorophosphate was used as the electrolyte (1 mol / L LiPF6 / EC:DEC, the volume ratio of EC and DEC was 1:1), and Celgard 2400 polypropylene film was used as the separator, and a button-type lithium-ion battery was assembled in a glove box with oxygen and water contents less than 0.1 ppm. At a current density of 0.5 C, the obtained battery has a capacity of up to 1210 mAh g -1 The weight specific capacity of the battery can reach 89% after 200 cycles, which shows excellent cycle stability.
[0052] From the comparison of the results of Examples 1-3 and Comparative Examples 1-2, it can be seen that the high-entropy stabilized shell enhances the interfacial stability of the silicon negative electrode and constructs a highly stable interfacial charge transfer network. When used as a lithium battery negative electrode, it exhibits high charge and discharge specific capacity and extremely excellent cycle stability. At the same time, the method of the present invention is low-cost, simple in process, low in energy consumption, scalable, and compatible with commercial battery electrode preparation processes.
Claims
1. A highly stable core-shell structure silicon negative electrode material, characterized in that: The negative electrode material comprises a high-capacity silicon core and a high-entropy stable shell; The high entropy shell is formed in situ by mechanical mixing of different elemental single substances and (or) compounds and high-temperature heat treatment; the high entropy stable shell is chemically bonded to the high-capacity silicon core to form an integrated high-stability core-shell structure; In the negative electrode material, the thickness of the high entropy stabilization shell is 1-10 nm; In the negative electrode material, the high entropy stabilization shell contains no less than 5 types of elements.
2. The negative electrode material according to claim 1, characterized in that The silicon material includes any one of zero-dimensional silicon particles, one-dimensional silicon wires / tubes, or two-dimensional silicon wafers, or a mixture of at least two of them.
3. The negative electrode material according to claim 1, characterized in that The different element single substances and (or) compounds are any four elements of indium, tin, gallium, copper, zinc, phosphorus, sulfur, nitrogen, oxygen, carbon, tin oxide, phosphorus pentoxide, copper nitrate, zinc nitrate, copper sulfate, tin chloride, copper chloride, etc., and a mixture of the above single substances and (or) compounds.
4. The method for preparing the negative electrode material according to claim 1, characterized in that: The method comprises the following steps: The silicon negative electrode material and any four or more elements and (or) compounds are mechanically mixed, and then the uniform mixture is subjected to high-temperature heat treatment in a non-oxidizing atmosphere to obtain a core-shell structured silicon negative electrode material with a high-entropy stable shell layer.
5. The method according to claim 4, characterized in that The mixing equipment used for the mechanical mixing is any one of a propeller stirrer, a spiral stirrer, a mincer, a pulverizer, a crusher, and a ball mill; The mixing time is 10 min-24 h.
6. The method according to claim 4, characterized in that The heat treatment method is any one of high temperature furnace heating, Joule heating and microwave heating; The heat treatment temperature is 400°C-3000°C, and the heat treatment time is 10min-24h.
7. The method according to claim 4, characterized in that The non-oxidizing atmosphere is any one of nitrogen, argon, hydrogen, helium or carbon dioxide, or a combination of at least two of them.
8. A negative electrode active material, characterized in that: The negative electrode is the highly stable core-shell structure silicon negative electrode material as claimed in claim 1.
9. An electrochemical energy storage device and / or energy storage system, characterized in that: The electrochemical energy storage device and / or energy storage system comprises the highly stable core-shell structure silicon negative electrode material according to claim 1.